Molecular detection and genotyping of Enterocytozoon bieneusi in captive foxes in Xinxiang, Central China and its impact on gut bacterial communities. (December 2021) - Sui, Yuzhen; Tong, Chao; Li, Xinmiao; Zheng, Liping; Guo, Yunan; Lu, Ying; Huang, Shucheng; Wang, Haidong; Chen, Minghui; Xu, Chunyan; Dai, Hongyu; Liu, Fang; et al.
Abstract: Enterocytozoon bieneusi is a common gastrointestinal parasite that has a broad range of hosts, including birds, mammals, and even humans. The changes of gut bacterial communities have been demonstrated during the course of E. bieneusi . This study aimed to examine the infection status, and assess the zoonotic potential and influence of E. bieneusi on gut bacterial communities of captive foxes in Xinxiang, central China. Fecal samples were collected from 216 captive foxes, and amplification of the internal transcribed spacer (ITS) gene of each sample was performed by nested polymerase chain reaction. E. bieneusi was detected in 48 (22.2%) samples, and five previously reported genotypes CHN-F1 ( n  = 25), D ( n  = 18), BEB6 ( n  = 3), NCF2 (n = 1), and CHN-DC1 (n = 1) were identified, with CHN-F1 being the dominant genotype (25/48, 52.1%). Phylogenetic analysis further revealed that CHN-F1, D, NCF2, and CHN-DC1 genotypes belonged to the zoonotic group 1 of E. bieneusi, whereas BEB6 belonged to group 2. Moreover, sequencing and bioinformatics analysis of the V3–V4 region of 16S rRNA gene in five E. bieneusi -positive and five negative samples showed that gut microbial diversity was higher in the infected animals. In both groups, Firmicutes and Bacteroidetes were the two most abundant phyla, but the Firmicutes/Bacteroidetes ratio was lower in E. bieneusi -positive foxes (7.9:1) as compared with E. bieneusi -negative foxes (5:1). More importantly, at the phylum level, "beneficial bacteria" such as Firmicutes (1.6%) and Bacteroides (5.8%) increased, whereas "opportunistic pathogens" such as Fusobacteria (8.2%) decreased. Similarly, at the genus level, the pathogenic Clostridiaceae _Clostridium (10.0%) decreased, whereas the "beneficial bacteria" Lactococcus (6.6%) increased. These interesting phenomena warrant further investigation. Highlights: E. bieneusi CHN-F1 genotype is dominant in captive foxes in Xinxiang, Central China. E. bieneusi infection is associated to higher gut microbial diversity and lower Firmicutes/Bacteroidetes ratio. Effective strategies to prevent and control E. bieneusi transmission are warranted.